Final Cut Pro X professional video editing - Martin, Steve (Peachpit Press, 2011)
"Introducing the Apple Pro Video Series: Final Cut Pro X, the first Apple-Certified video on Final Cut Pro X. In this tutorial, Apple-certified master trainer Steve Martin, guides you through the new workflows, toolsets and features of Final Cut Pro X. Whether you are new to digital video editing or transitioning from another editing application, you will get a solid foundation for understanding the software. Apple Pro Video Series: Final Cut Pro X starts from the beginning and assumes no prior knowledge of Final Cut Pro or Mac-based video editing. The video tutorials walk you through the complete post production workflow, from initial media import to final output. Along the way you'll learn techniques to make you more productive using Final Cut Pro X's editing tools, effects, titles, transitions and themes. Previous experience with iMovie or legacy versions of Final Cut Pro is not required, however a solid foundation in those apps would prove to be a useful bridge to understanding Final Cut Pro X's new workflow paradigms. Each step in the editing workflow is presented in easy-to-follow learning modules. The training is presented in 37 individual lessons with a running time of 5 hours. Media files for following along in Final Cut Pro X are also included."--Resource description page.
Title from cover thumbnail image on resource description page (viewed Sept. 6, 2011). - Publication information from resource description page
Keywords: Final cut (Electronic resource); Motion pictures -- Editing -- Data processing; Digital video -- Editing -- Data processing; Montage (Cinéma); Informatique; Vidéo numérique; Montage; Informatique; Digital video; Editing; Data processing; Motion pictures; Editing; Data processing